PENGUATAN LOCAL WISDOM MASYARAKAT KEPULAUAN DALAM MENCEGAH WABAH MELALUI KKN-DR - Samsul Arifin; Miftahul Alimin; Siti Hartatik; Indah Ulil Firdausiyah; Nur Aini (As-Sidanah, 2021)
This outreach program aimed to recognize and strengthen local wisdom of the people in Sapudi Island, Madura in preventing plague (tolak-balak). The community service method uses Participatory Action Research (PAR). The results show that the people of Sapudi Island in preventing disease outbreaks include: doing Rokat Pandhaba, Burdah Keliling Kampong, and other ritual or celebration. The purpose of the celebration is to get closer to Allah and to familiarize relationships with the community and the environment in order to avoid disasters and calamities. By doing harmonization between God, human beings, and the environment, people feel that they have achieved meaning in life (meaningfullnees). This paper was useful for developing theories of mental health, psychology, and counseling which are resulted from the values of the locality of the archipelago.